Skills and Physical Literacy Activities of Primary School Age Children - Muhammad Yusron Afandi; Agung Yuda Aswara; Susilo Bekti (Universitas Negeri Semarang, 2024)
At the age of elementary school children, they should still be doing physical activities more actively. But in reality, the development of technology has made them more lazy in doing physical activities. The purpose of this study is to provide an understanding of physical literacy for elementary school children where this factor is one of the foundations that must be implemented properly. This research is a comparative causal research with a quantitative approach. In this study there are two samples to be studied, namely class teachers and physical education, sports and health teachers. The instrument in this study used a questionnaire that contained a list of questions regarding the independent variable about the perception of the level of physical literacy skills of elementary school children according to class teachers and physical education, sports and health teachers. This instrument uses a Likert scale with 10 alternative answers. The subjects in this study were class teachers and physical education, sports and health teachers totaling 78 teachers, 21 class teachers with details of 16 female teachers and 5 male teachers and 57 physical education, sports and health teachers with details of 19 women and 38 men. The youngest respondent teacher was 20 years old and the oldest was 57 years old. The research results are: 1) The level of physical literacy skills of primary school-age children according to class teachers shows good qualifications with a value of 4 with a range of values of 97.1905; 2) The level of physical literacy skills of primary school-age children according to physical education teachers shows good qualifications with a value of 4 with a range of values of 106.6; 3) From the results of the calculation there is no difference in the average level of physical literacy skills of primary school-age children according to class teachers and according to physical education teachers. The conclusion of this study is that the overall level of physical literacy skills of elementary school children according to class teachers and physical education teachers shows good qualification results.